MEMBANGUN KEMANDIRIAN : PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PROGRAM RUMAH PADAT KARYA - Ajiputri, Adhiva Calista; Hardjati, Susi (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2024)
Empowering the poor as an alternative to overcoming poverty in the city of Surabaya with the aim of building community independence through utilizing their potential to meet their living needs independently. The purpose of this research is to determine the implementation of the process and achievement of community empowerment goals through the Prapen Work-Intensive Housing program, Tenggilis Mejoyo District, Surabaya City. This research uses descriptive qualitative research methods with data collection techniques through observation, interviews and documentation. The results of the research show that: (1) Pemungkinan theory were done through providing motivation, but motivation has not completely made the training participants aware. (2) Penguatan theory is carried out through training activities, however the provision of skills is not yet fully capable of improving the ability to manage the business. (3) Perlindungan theory is carried out through expanding market access, but market access is only for laundry businesses. (4) Penyongkongan theory is carried out through mentoring, however mentoring is not carried out intensively so that problems that hinder the business still cannot be resolved. (5) Perlindungan theory is carried out through monitoring and evaluation activities, but this does not yet fully maintain the balance of efforts and harmony of each workforce in running the Rumah Padat Karya Prapen business. In this case, the empowerment of poor communities through the Rumah Padat Karya program in Prapen has not run optimally, as there is no independence capability for the business workforce in managing and developing the business independently.